Examining housing discrimination across race, gender and felony history. Issue 5 (28th May 2019) - Evans, Douglas N.; Blount-Hill, Kwan-Lamar; Cubellis, Michelle A.
Abstract: Those who have been convicted of crimes are subjected to a stigma that affects many aspects of their social lives. The "felon" label brings collateral consequences that make it difficult to obtain basic human needs, including housing. This study uses the audit method to examine the effects of race, gender, and criminal history on housing outcomes. Testers, exhibiting characteristics suggestive of race and gender and disclosing one of three offenses, placed phone calls to rental property owners across the Midwest to inquire about renting a property. We found powerful negative effects for those with a criminal record seeking apartments, regardless of whether the offense was sexual or drug-related. However, we found no differences between minority and non-minority testers. We explain these findings in the context of housing as an essential resource for formerly incarcerated individuals.